Analysis of Wnt/FZD-mediated signalling in a cell line model of colorectal cancer morphogenesis - Vincan, Elizabeth; Whitehead, R.; Faux, M. (Humana Press, 2008)
Cells in tissues do not exist as isolated entities but are part of the three-dimensional tissue architecture. Consequently, some aspects of cell behaviour cannot be mimicked by simple in vitro monolayer culture systems. Moreover, cell shape and behaviour is not rigid but is dynamic and can be regulated by intrinsic and extrinsic factors. For example, tumour cells in epithelium-derived cancer such as colorectal cancer often retain significant features of the colonic mucosa. However, as the tumour progresses, the morphology of the tumour cells often undergoes a transition from an epithelial morphology to a mesenchymal morphology. This transition is important as it signifies a change in the tumour phenotype to a more aggressive, invasive, and eventually metastatic phenotype. In vitro models that allow the study of this transition are needed. One such model is the LIM1863 colon carcinoma cells that normally grow as organoids but can be adapted to efficiently undergo an epithelial to mesenchymal transition that can be reversed. This system has allowed the study of the genes such as Frizzled 7 that are involved in this dynamic and reversible epithelial to mesenchymal transition. © 2009 Humana Press.